Perianchor Cyst Formation Is Similar Between All-Suture and Conventional Suture Anchors Used for Arthroscopic Rotator Cuff Repair in the Same Shoulder - Elliott W. Cole, M.D., M.P.H; Brian C. Werner, M.D; Patrick J. Denard, M.D (Elsevier, 2022)
Purpose: The purpose of this study was to compare perianchor cyst formation between soft and hard suture anchors placed in the same patient 1 year after arthroscopic rotator cuff repair (ARCR). Methods: This study reviewed patients who underwent primary ARCR using a "hybrid" technique using at least one soft anchor (FiberTak, Arthrex, Naples, FL) and one hard anchor (SwiveLock) placed in the same shoulder between January 1, 2018 and December 31, 2018. Magnetic resonance imaging was obtained at minimum 1-year postoperative to assess cyst formation (perianchor fluid signal) and rotator cuff healing. Range of motion (ROM) and patient-reported outcome measures (PROMs) were evaluated at baseline and 1-year follow up. PROMs included visual analog scale pain score, Simple Shoulder Test score, American Shoulder and Elbow Surgeon (ASES) score. Results: Nineteen patients with a combined 45 hard and 26 soft suture anchors were available for follow-up at a mean of 20 months postoperatively. There was a higher proportion of grade 1 fluid signal changes in the hard anchor group compared to the soft group (62.2% to 7.7; P < .001); however, there was no difference in the incidence of cyst formation (grade 2 or 3 changes) between groups (13.3% vs 3.8%; P = .251). There was also no difference in the rate of cyst formation between biocomposite and polyether-ether-ketone-type hard anchors (18.2% vs 0%; P = .113) or between anchors placed at the greater and lesser tuberosities (10.2% vs 5.3%, P = .519). Conclusion: Hard suture anchors showed increased fluid signal compared to soft suture anchors at short-term follow-up after ARCR, but there was no difference in cyst formation between anchor types.